PERENCANAAN POLA USAHA PETERNAKAN SAPI POTONG RAKYAT DENGAN PROGRAM INTEGER DI KABUPATEN LAMPUNG TENGAH - Imron, Agus (Indonesian Journal of Socio Economics)
The objectives of this study are to know the efficiency of resource use and make an optimal planning of the cattle breeding pattern business in the Lampung Tengah district. Primary data were collected through interviews with cattle breeders. The sample breeders were drawn by Simple Random Sampling Technique. Fourty cattle breeders were interviewed. The main analysis in this study was done by Integer Programming. The study found thatÂ  the cattle breeders have not used their resources efficiently. This fact was indicated by the achievment which was not optimal. According the optimal plan, the breeders income will rise from Rp15.176.243,07/year to Rp18.553.650,00/year. In the optimal planning, the cattle breeders should breed 6,00 tail of PIR KKP cattles, 14,00 tail of own famale cattles, and shared 6,00 tail of PIR Swadana cattles.